Total Flavonoid Content and Antioxidant Properties of Different Extraction Methods of Red Spinach Leaf (Amaranthus tricolor L.) - Permanasari, Etin Diah; Amalia, Mega Putri Rizky; Susilo, Susilo; Prastiwi, Rini (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Red spinach leaf (Amaranthus tricolorÂ L.) has been well-proven to contain flavonoids that exhibit antioxidant activities. In this study, a comparison between maceration and ultrasonic methods has been carried out to evaluate the effect of these two methods on the level of red spinach leaf flavonoid. In this study, for maceration 1, 2, and 3 days while for the ultrasonic method 10-, 20-, and 30-minutes time duration have been used. The ratios of material and solvent were 1:5 and 1:10. The flavonoid content was determined with the help of a spectrophotometer at a maximum wavelength of 436.80 nm. The antioxidant activity was evaluated by the DPPH method to obtain the IC50. The result of the study revealed that the highest flavonoid content of 4.27 mgQE/g and antioxidant activity (IC50) of 110.47 ppm were obtained by an ultrasonic under conditions of 1:10 ratio and 30-minute extraction time. Results of the study suggested a significant difference (p<0,05) in the isolation of total flavonoid contents and antioxidant activities in the maceration and ultrasonic. In these two methods, ultrasonic was found to be more efficient than maceration because of minimum time, the highest flavonoid content and antioxidant activity could be obtained.